De novo assembly of two chromosome-level rice genomes and bin-based QTL mapping reveal genetic diversity of grain weight trait in rice - Kong, Weilong; Deng, Xiaoxiao; Liao, Zhenyang; Wang, Yibin; Zhou, Mingao; Wang, Zhaohai; Li, Yangsheng (Frontiers in Plant Science, 2022)
Following the "green revolution", indica and japonica hybrid breeding has been recognized as a new breakthrough in further improving rice yields. However, heterosis-related grain weight QTLs and the basis of yield advantage among subspecies has not been well elucidated. We herein de novo assembled the chromosome level genomes of an indica/xian rice (Luohui 9) and a japonica/geng rice (RPY geng) and found that gene number differences and structural variations between these two genomes contributes to the differences in agronomic traits and also provides two different favorable allele pools to produce better derived recombinant inbred lines (RILs). In addition, we generated a high‐generation (>F15) population of 272 recombinant inbred lines from the cross between Luohui9 and RPY geng and two testcross hybrid populations derived from the crosses of RILs and two cytoplasmic male sterile lines (YTA, indica and Z7A, japonica). Based on three derived populations, we totally identified eight 1000-grain weight (KGW) QTLs and eight KGW heterosis loci. Of QTLs, qKGW-6.1 and qKGW-8.1 were accepted as novel KGW QTLs that have not been reported previously. Interestingly, allele genotyping results revealed that a heading date related gene in qKGW-8.1 and qLH-KGW-8.1, Ghd8, can affect grain weight in RILs and rice core accessions and may also play an important role in grain weight heterosis. Our results provided two high-quality genomes and novel gene editing targets of grain weight for future rice yield improvement project.